2021
DOI: 10.1136/bmjopen-2020-044949
|View full text |Cite
|
Sign up to set email alerts
|

Association between postsurgical pain and heart rate variability: protocol for a scoping review

Abstract: IntroductionSurgical interventions can elicit neuroendocrine responses and sympathovagal imbalance, ultimately affecting cardiac autonomic function. Cardiac complications account for 30% of postoperative complications and are the leading cause of morbidity and mortality following non-cardiac surgery. One cardiovascular parameter, heart rate variability (HRV), has been found to be predictive of postoperative morbidity and mortality. HRV is defined as variation in time intervals between heartbeats and is affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Decreases in HRV 6 weeks after surgery may be associated with the acute effects of the operation including: surgical manipulations, prolonged aortic cross-clamping, use of ice slush, ischemia or dysfunction of cardiac ANS regulation post-CABG [ 32 , 33 , 34 ]. Anxiety about the danger and the pain of the surgery are also likely also to contribute to the reduction in HRV [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Decreases in HRV 6 weeks after surgery may be associated with the acute effects of the operation including: surgical manipulations, prolonged aortic cross-clamping, use of ice slush, ischemia or dysfunction of cardiac ANS regulation post-CABG [ 32 , 33 , 34 ]. Anxiety about the danger and the pain of the surgery are also likely also to contribute to the reduction in HRV [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…A flow diagram of the search results is shown in Figure 1. A detailed search of MEDLINE and EMBASE was conducted according to our published protocol 57 and yielded 230 records. No additional studies were identified in clinical trial registries or reference lists of included studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…The review protocol has been previously published 57 and was written in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis. 45…”
Section: Methodsmentioning
confidence: 99%